Modern approaches to diagnosis and surgical treatment of patients with acute obstructive intestinal obstruction - V. A. Samartsev; B. S. Pushkarev; V. A. Gavrilov; A. A. Parshakov; M. P. Kuznetsova; A. A. Domrachev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of the study was to improve the results of surgical treatment of patients with acute obturation intestinal obstruction of tumor and non-tumor origin by improving the algorithm for perioperative diagnosis and treatment of complications.METHODS AND MATERIALS. A single-center retrospective-prospective study of the results of treatment of patients with acute obturation intestinal obstruction (n=249) was conducted. The comparison group (n=125) was represented by a retrospective sample of patients whose examination and surgical treatment were carried out in accordance with the established procedure for providing medical care. Observation group (n=124): patients whose examination and surgical treatment were supplemented by assessment of the degree of compensation for acute obturation intestinal obstruction, the use of specialized scales, computer monitoring of intra-abdominal pressure and intraoperative assessment of microcirculation in the wall of the colon in patients with acute obturation intestinal obstruction (AOIO) using original methods.RESULTS. In the observation group, the time from admission to the hospital to surgical treatment was less than in the comparison group and amounted to 6.00 (Q1–Q3: 4.00–8.00) hours and 10.00 (Q1– Q3: 6.00–12.00) hours, respectively, (p <0.0001), mainly due to patients with a subcompensated form. Mortality in patients with acute obturation intestinal obstruction of tumor origin in the observation group was 11 (12.94 %) patients, in the comparison group – 16 (18.18 %) patients; non-tumor origin in the observation group – 8 (20.51 %), comparison – 10 (27.03 %) patients. Based on the conducted studies, an algorithm for perioperative diagnosis and treatment of complications was proposed.CONCLUSION. The differentiated choice of surgical tactics for acute obturation intestinal obstruction makes it possible to optimize the timing of surgical intervention, reduce the number of postoperative complications, as well as mortality in patients with acute obturation intestinal obstruction of tumor and non-tumor origin.